Auxin Directly Upregulates GhRAC13 Expression to Promote the Onset of Secondary Cell Wall Deposition in Cotton Fibers - Zhang, Mi; Cao, Huizhen; Xi, Jing; Zeng, Jianyan; Huang, Juan; Li, Baoxia; Song, Shuiqing; Zhao, Juan; Pei, Yan (Frontiers in Plant Science, 2020)
Cotton fibers are single cells possessing of relatively independent developmental processes of cell differentiation, elongation and secondary wall deposition. Plant hormone auxin promotes fiber cell protrusion from ovule surface. However, little is known regarding roles of auxin in the other developmental stages of cotton fibers. To this end, we measure IAA content in developing fibers and exhibit an increase in transition stage from elongation to secondary cell wall deposition. This urges us to investigate two transgenic cottons respectively upregulating and downregulating auxin level in fibers. In planta analysis reveals that, in addition to promoting cell elongation, auxin regulates appearance timing of ROS (reactive oxygen species) production and secondary wall deposition in cotton fibers. This is correlated to upregulated expression of GhRAC13, which regulates ROS-triggered cellulose synthesis.Furthermore, we find multiple putative auxin response elements within the promoter region of GhRAC13.Under inducement of IAA, the major auxin in plants, the activity of proGhRAC13 is considerably upregulated. Dual-luciferase reporter assay further proves the activation of proGhRAC13 by GhARF5, an auxin signaling activator. Taken together, our result suggests a role of auxin in promoting the onset of secondary growth through directly upregulation of GhRAC13 expression in cotton fibers.